Prediktor Kesiapan Kerja Siswa SMK di Era Disrupsi: Kontribusi Efikasi Diri dan Literasi Digital - Ilhami Chusnunia Qori; Theodorus Wiyanto Wibowo; Puput Wanarti Rusimamto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The acceleration of Industry 4.0 has transformed the qualifications required of the automotive workforce, requiring vocational graduates to possess not only technical competence but also digital proficiency and psychological resilience. This study examines the influence of self-efficacy and digital literacy on the work readiness of 104 twelfth-grade students in the Light Vehicle Engineering (TKR) program. A quantitative approach with total sampling was employed, using a four-point Likert-scale questionnaire analyzed through multiple linear regression in Stata 17. Descriptive results indicate that self-efficacy, digital literacy, and work readiness are at a moderate-to-high level. Partial hypothesis testing reveals that self-efficacy has a positive and significant effect on work readiness (β = 0.5108, p < 0.05), as does digital literacy (β = 0.5890, p < 0.05). Simultaneously, both variables explain 53.34% of the variance in work readiness (F = 57.72, p < 0.001). These findings highlight that the synergy between internal self-belief and digital competence is a critical predictor of career resilience amid technological disruption. This study recommends integrating self-efficacy and digital literacy through Project-Based Learning (PjBL) and collaborative inquiry to enhance students’ work readiness in a competitive global labor market.